2003
DOI: 10.1507/endocrj.50.603
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Highly Purified Eicosapentaenoic Acid Ethyl Ester Improves Blood Coagulation Abnormalities and Dysfunction of Vascular Endothelial Cells in Otsuka Long-Evans Tokushima Fatty Rats

Abstract: Abstract. We investigated the effect of highly purified eicosapentaenoic acid ethyl ester (EPA-E) on blood coagulation abnormalities and dysfunction of vascular endothelial cells in spontaneously diabetic Otsuka Long-Evans Tokushima Fatty rats. The animals were treated with either EPA-E or lard at a daily dose of 0.3 g/kg/day for 52 weeks by gavage, and their coagulation/fibrinolytic parameters, platelet aggregation, and functions of the vascular endothelial cells were examined. EPA-E significantly improved co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Thus, the increase of adiponectin by EPA may exert a platelet-inhibitory effect via nitric oxide. EPA has been reported to play a role in coronary events in hyperlipidemic patients 27) , and its biological functions include the reduction of platelet activation 25,48) , endothelial factors [49][50][51] , and inflammatory markers in metabolic syndrome 52) . Our results suggest that EPA possesses multifunctional anti-thrombotic properties, and that its action is dependent on adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increase of adiponectin by EPA may exert a platelet-inhibitory effect via nitric oxide. EPA has been reported to play a role in coronary events in hyperlipidemic patients 27) , and its biological functions include the reduction of platelet activation 25,48) , endothelial factors [49][50][51] , and inflammatory markers in metabolic syndrome 52) . Our results suggest that EPA possesses multifunctional anti-thrombotic properties, and that its action is dependent on adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with safflower oil feeding, EPA-fed diabetes-prone rats were leaner, had lower blood lipid levels, and a blunted insulin response to glucose testing ( Minami et al 2002 ). Another study in the same rat model found platelet response to ADP and collagen reduced, and a number of coagulation and fibrinolysis parameters altered towards a less procoagulatory state ( Mori, Nobukata, et al 2003 ). Also, migration activity of vascular endothelial cells was increased, and binding of vascular endothelial cells to vascular endothelial cell growth factor decreased ( Mori, Nobukata, et al 2003 ).…”
Section: Animal Modelsmentioning
confidence: 99%
“…The effect of hormonal regulation on hemodynamic parameters and atherosclerotic risk factors have also been assessed in womens taking progestin containing contraceptives [606], and testosterone treated rabbit model [609]. Besides this many animal models of thrombosis are also available which can be used to assess the hypercoaguability and thrombogenecity of blood under hyperlipidemic conditions in the presence and absence of test compounds [339,340,445,[610][611][612].…”
Section: Thrombosis Potentialmentioning
confidence: 99%